A rare reason in a child with feeding intolerance: Intravaginal struvite stone - Yavuz Tokgöz; Ali Onur Erdem; Bilge Canan Özbey; Semiha Terlemez (The Turkish Journal of Pediatrics, 2018)
Vaginal stones are rarely seen in childhood; they are categorized as primary and secondary whether they are a foreign object focus (nidus) or not. Urethrovaginal fistula is the most common etiological cause; other etiologies are considerably rarely reported. Primary vaginal stones are formed as a result of urinary salt accumulate. A 14-year-old girl, suffering from an unidentified neurodegenerative disease, was admitted with complaints of cough, poor feeding and vomiting. Abdominal X-ray showed a large calcific mass; further evaluation revealed a vaginal struvite stone, and it was removed surgically. No anatomical reason was determined for the formation of stone and it was accepted as primary vaginal stone.